Effects of information, education, and communication campaign on a community-based health insurance scheme in Burkina Faso - Cofie, Patience (Co-Action Publishing, 2013)
OBJECTIVE: The study analysed the effect of Information, Education, and Communication (IEC) campaign activities on the adoption of a community-based health insurance (CHI) scheme in Nouna, Burkina Faso. It also identified the factors that enhanced or limited the campaign's effectiveness. DESIGN: Complementary data collection approaches were used. A survey was conducted with 250 randomly selected household heads, followed by in-depth interviews with 22 purposively selected community leaders, group discussions with the project management team, and field observations. Bivariate analysis and multivariate logistic regression models were used to assess the association between household exposure to campaign and acquisition of knowledge as well as household exposure to campaign and enrolment. RESULTS: The IEC campaign had a positive effect on households’ knowledge about the CHI and to a lesser extent on household enrolment in the scheme. The effectiveness of the IEC strategy was mainly influenced by: (1) frequent and consistent IEC messages from multiple media channels (mass and interpersonal channels), including the radio, a mobile information van, and CHI team, and (2) community heads’ participation in the CHI scheme promotion. Education was the only significantly influential socio-demographic determinant of knowledge and enrolment among household heads. The relatively low effects of the IEC campaign on CHI enrolment are indicative of other important IEC mediating factors, which should be taken into account in future CHI campaign evaluation. CONCLUSION: The study concludes that an IEC campaign is crucial to improving the understanding of the CHI scheme concept, which is an enabler to enrolment, and should be integrated into scheme designs and evaluations.